2002
DOI: 10.2174/1381612024606983
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Clinical Significance of Endotoxemia in the Course of Hepatitis C Virus Infection

Abstract: Endotoxins or lipopolysaccharides (LPS), major components of the cell wall of Gram-negative bacteria, once released from the bacterial outer membrane bind to specific receptors and, in particular, to a membrane-bound receptor, the CD14 (mCD14) and the toll-like receptor 4 present on monocytes/ macrophages. In turn, LPS-activated monocytes/ macrophages release in the host tissue an array of so-called proinflammatory cytokines and, among them, Tumor Necrosis Factor (TNF)-alpha, interleukin (IL)-1beta, IL-6, IL-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 0 publications
4
41
0
3
Order By: Relevance
“…Here we showed that HCV core protein, a TLR2 ligand (6,7), activated and induced tolerance in normal but not in cHCV monocytes. We also identified increased levels of endotoxin, a TLR4 ligand, in plasma of patients with cHCV infection, which is in agreement with previous reports (26). It is noteworthy that cHCV patients included in our study did not exhibit liver cirrhosis, yet low levels of endotoxemia occurred in patients with cHCV without advanced liver disease.…”
Section: Discussionsupporting
confidence: 93%
“…Here we showed that HCV core protein, a TLR2 ligand (6,7), activated and induced tolerance in normal but not in cHCV monocytes. We also identified increased levels of endotoxin, a TLR4 ligand, in plasma of patients with cHCV infection, which is in agreement with previous reports (26). It is noteworthy that cHCV patients included in our study did not exhibit liver cirrhosis, yet low levels of endotoxemia occurred in patients with cHCV without advanced liver disease.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, LPS has been shown to accelerate liver fibrosis through TLR-4 signaling on Kupffer cells following membrane binding via LPS binding protein (LBP) and CD14 (121). These events lead to the generation of superoxide and the release of proinflammatory and profibrogenic cytokines such as TNF-␣, IL-1, IL-6, and IL-12, all of which induce liver damage (122,123). Consistent with these findings, microbial translocation has been shown to contribute to liver disease in several clinical settings, such as alcoholic liver disease (124,125) and other enteric processes (126)(127)(128).…”
Section: Microbial Translocation In Liver Diseasementioning
confidence: 99%
“…93 Indeed, damage to the GI tract has been observed to result in the luminal translocation of microbial products such as lipopolysaccharide (LPS), peptidoglycan, bacterial CpG DNA, flagellae, and viral genomes: molecules that can directly stimulate the innate immune system through Toll-like receptors. This process, termed microbial translocation, has been observed in numerous diseases, including ulcerative colitis and Crohn's disease, 94 graft-versus-host disease, 95 and hepatitis 96 as well as after abdominal surgeries 97 and in pancreatitis. 98 Importantly, in many of these situations the microbial translocation is associated not only with local inflammation of the gut microenvironment but also with systemic immune activation.…”
Section: Enteropathy Revisitedmentioning
confidence: 99%